MUATAN KEMAHIRAN BERBAHASA INDONESIA DALAM MEDIA WEBSITE SEBAGAI PENGUATAN PEMBELAJARAN BERBASIS TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE - Kurniawan, Andriyanto; Sudiyana, Benedictus; Nurnaningsih (UNIVERSITAS PGRI YOGYAKARTA, 2024)
The aim of this research is to describe aspects of Indonesian language proficiency that can be developed or captured through the use of websites to strengthen TPACK-based learning in junior high schools. The research method uses qualitative descriptions. The data used are aspects of language proficiency that are attached to the website content. The data sources used are websites in the form of social media, government organizations, online communities, market content, Google Chrome/information, technology, health and education. The findings in this research are: 1) aspects of language proficiency are increasingly attached to the implementation of Indonesian language learning in junior high schools through website media. 2) The language skills produced by students become more proficient and competitive, including aspects of speaking, writing, listening and reading by utilizing website pages as a medium for language learning at school. 3) The names of websites used in Indonesian language learning as reinforcement for TPACK-based learning include kejarcita.id, Ruang Guru, Zenius, Rumah Belajar Kemendikbud, Ilmu Pintar.id, Indonesia Montessori, e-learning platform and Google Chrome which is focused on aspects content of Indonesian language skills. The conclusion of this research is that the content of students' language proficiency in learning Indonesian in junior high school can be studied and actualized in real terms by utilizing website pages as reinforcement for TPACK-based learning in accordance with the concept of 21st century education